The Impact of Mandatory IFRS Adoption on Earnings Management: Evidence from France - BASMA BEN NEFISSA (Indonesian Management and Accounting Research, 2025)
This study investigates the effect of mandatory IFRS adoption on earnings management in France using panel data from the SBF 120 index (n = 979) over two periods: pre-IFRS (2002–2005) and post-IFRS (2006–2016). Employing the earnings smoothing model developed by Ball et al. (2008), this research evaluates changes in the quality of accounting information by analyzing the variability of net income relative to other firm-specific variables. The results indicate a significant reduction in earnings management following the adoption of IFRS, evidenced by increased variability in net income and decreased smoothing behavior. These findings suggest that mandatory IFRS adoption contributes to more transparent financial reporting and enhances the credibility of accounting information in the French context. The study provides valuable insights for stakeholders, particularly companies in jurisdictions that have not yet adopted IFRS.